Management of massive and irreparable rotator cuff tears: an evidence-based review of joint-preserving treatment strategies - Shiwtarkar, Karan S.; Rathi, Pranav P.; Devpura, Mukesh M. (International Journal of Research in Orthopaedics, 2026)
Massive and irreparable rotator cuff tears are associated with substantial pain, weakness, and altered shoulder biomechanics. For younger or physically active individuals, surgeons typically prefer joint-preserving operations instead of arthroplasty to keep the original anatomy intact and postpone the need for prosthetic implants. This systematic review evaluates functional outcomes, range of motion, structural integrity, and complications of contemporary joint-preserving surgical options for massive and irreparable rotator cuff tears. A comprehensive search was performed according to PRISMA 2020 guidelines. Studies reporting outcomes of superior capsular reconstruction, tendon transfers, patch augmentation, graft interposition, long head of the biceps augmentation, and subacromial balloon spacers were included. Owing to heterogeneity, qualitative synthesis was conducted. Superior capsular reconstruction, particularly with fascia Lata autograft, demonstrated the most consistent improvements in functional scores and forward elevation. Tendon transfers, especially latissimus dorsi transfer, improved external rotation in selected patients. Patch augmentation and graft interposition reduced re-tear rates compared with partial repair. Less invasive options showed symptomatic benefit but variable structural durability. Joint-preserving procedures offer meaningful clinical improvement; however, further high-quality comparative trials are necessary.